Experimental Study Of The Effect Of Granite Cutting Waste As Partial Replacement Of Cement - Anor, Nur Ilmadiena (Universiti Sains Malaysia, 2022)
Increasing social demands increases waste production. Research claim that 20-30% of global granite production is a waste currently stacked in landfills and can be used in cement making. Furthermore, Ordinary Portland Cement (OPC) is infamous for requiring high sintering temperatures (1450°C), resulting in high energy consumption and carbon dioxide (CO2) emissions. The purpose of this work is to analyse Granite Cutting Waste (GCW) as cement partial replacement and to establish ideal conditions for the synthesis of an eco-friendly cement. Firstly, GCW was characterised using Scanning Electron Microscopy (SEM), .Particle Size Analysis (PSA), X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD). The OPC and eco-friendly cement(GC) is then prepared to a specified mineralogical composition and sintered at different temperatures of 1000°C, 1100°C, 1200°C and 1300°C. The final sample were analysed. Results show that GCW are suitable in cement because it has an elongated and irregular shape and existence of microcline and anorthite crystal phases that shows GCW pozzolanicity. As a result, this demonstrates that granite cutting wastes can be employed as raw materials in the production of environmentally friendly cements. Moreover, the best sintering temperature for eco-friendly cement was discovered to be 1100 °C because hydraulic active compounds like larnite and brownmillerite were dominant in the products while OPC optimum temperature were at 1300 °C. The knowledge gathered from this work will be hugely beneficial for industrial progress in the years leading up to the 2030 Sustainable Development Goals (SDG).